2019
DOI: 10.1108/jmtm-02-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Circular business models generation for automobile remanufacturing industry in China

Abstract: Purpose Although China can be considered an early adopter of the circular economy, there are few studies of remanufacturing business models (BMs) in the context of the Chinese automobile industry. The purpose of this paper is to investigate viable BMs, summarizes current obstacles and anticipates future development opportunities and directions. Design/methodology/approach The cross-case analysis considers the roles of value networks and of customer value proposition and interface in circular business models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 78 publications
0
65
0
Order By: Relevance
“…The feedback information (see Figure 3) could be used to design products and components in a way that makes remanufacturing execution much easier, faster, efficient and more inexpensive. Past literature (e.g., [21][22][23][24][25]) has identified several barriers for remanufacturing that include the following: (1) Sufficient volume of the same kind of product is required to be able to run a manufacturing facility. Therefore, a consistent and smooth flow of incoming products for remanufacturing is vital.…”
Section: Remanufacturingmentioning
confidence: 99%
“…The feedback information (see Figure 3) could be used to design products and components in a way that makes remanufacturing execution much easier, faster, efficient and more inexpensive. Past literature (e.g., [21][22][23][24][25]) has identified several barriers for remanufacturing that include the following: (1) Sufficient volume of the same kind of product is required to be able to run a manufacturing facility. Therefore, a consistent and smooth flow of incoming products for remanufacturing is vital.…”
Section: Remanufacturingmentioning
confidence: 99%
“…Previous studies have suggested that business model innovation is a valuable source of competitive advantage that can lead to superior firm performance (Huang et al , 2013; Visnjic et al , 2016). Elsewhere in the literature (Audretsch et al , 2014; Love and Roper, 2015), business model innovation is seen as a specific type of innovation that is critical to the success of manufacturing firms, and a well-functioning business model is claimed to be a core driver of performance (Shao et al , 2019; Taran et al , 2015). Kim and Min (2015) suggested that asset reconfiguration through adding a new business model creates opportunities for competitive advantage, while Cucculelli and Bettinelli (2015) and Futterer et al (2018) found that modifying the business model in an innovative way has a positive effect on financial performance.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Yet, as Foss and Saebi (2017, 2018) noted, few studies have provided rigorous evidence of the performance implications of business model innovation, which in turn leaves unanswered the question of whether a change of business model really leads to benefits for the firm. This question is an important one for small- and medium-sized enterprises (SMEs) in manufacturing sectors as they have fewer resources and capabilities to help them mitigate the risks of reinventing and reconstructing their business model (Müller, 2019; Shao et al , 2019). Given the prominent economic contribution of manufacturing SMEs globally (Memili et al , 2015), it is critical to empirically ascertain whether manufacturing SMEs that adopt business model innovation can achieve better performance.…”
Section: Introductionmentioning
confidence: 99%
“…The interconnectedness of modern industrial and manufacturing enterprises is increasingly realised by their use and deployment of cloud based data collection and analysis systems through IoT (Tao et al, 2014). The automotive sector is strongly moving towards looking at the whole lifecycle aspects of the components used in vehicles and manufacturers increasingly design products for reusability and remanufacture (Shao et al, 2019). Therefore, this paper examines current practice of integrating digital maintenance within production and takes steps towards formulating a digital maintenance framework for automotive manufacturing.…”
Section: Introductionmentioning
confidence: 99%